Obstetricians'Attitudes toward Epidural Analgesia for Labor in a Single University Hospital in Thailand - Patchareya Nivatpumin (2022)
Objectives: To elucidate obstetricians' attitudes toward epidural analgesia for labor regarding maternal outcomes and complications and to describe commentaries about the use of epidural analgesia. Materials and Methods: This was a questionnaire paper-based, cross-sectional study. The questionnaire was made available over the period of February 2020 to August 2020. The questionnaire comprised 25 items and used a 5-point Likert scale for the responses. The respondents' attitudes stratified by their subspecialty, position (residents or graduate obstetricians), and work experience were also analyzed. Results: Out of 124 obstetricians working in our institute, 75 completed and returned the questionnaire, for a response rate of 60.5%. Among the respondents, 44 (58.7%) agreed that patients with vaginal labor should receive epidural analgesia if there are no contraindications. Most the obstetricians agreed that epidural analgesia for labor prolonged the second stage of labor (71.2%) and led to an increased rate of instrumental delivery (67.1%). On the other hand, only 31.5% agreed that epidural analgesia increased the rate of cesarean delivery. Obstetricians in the maternal-fetal medicine subspecialty reported significantly more experience with epidural analgesia cases than the other specialties (p < 0.001). The mean overall satisfaction score regarding the epidural analgesia for labor in our institute (0-100) was 68.2±15.8. Conclusion: This study revealed that a high proportion of obstetricians believed that epidural analgesia for labor mainly affects labor outcomes including the mode of delivery and side effects. There is also a need to ensure all staff involved in the labor suite have a greater understanding of various aspects regarding the use of epidural analgesia for labor.